Kidney Injury in Multiple Myeloma; Predisposing Factors, Manifestations & Outcome, Single Center Experience - Ahmed, Masser; Seddik, Ayman; Gulzar, Kashif; Alalawi, Fakhriya; Amar, Hadil M.; Salama, Sherian Musbah; Al Olama, Asma; AlHadari, Amna Khalifa (British Journal of Healthcare and Medical Research, 2026)
Introduction: Multiple Myeloma (MM) is third most common hematological malignancy. Renal impairment is observed in 25-75% patients with MM, could be due to disease itself or other unrelated causes, also its second most common cause of death after infection in MM patients. Purpose of this study is to compare clinical & lab parameters of multiple myeloma patients with & without kidney injury also to determine outcome of kidney injury. Results: Between 2017 to 2024, thirty-two patients were diagnosed with MM, their mean age was 61.62±12.05 years, and 78.12% were male. . Hypertension (n=11, 34.37%) & diabetes mellitus (n=7, 21.87%) were most common co morbid, and body aches/weakness (62.50%), fractures (17.64%) & anemia (17.64%) were common manifestations. Anemia, hypocalcemia, hypercalcemia & hypoalbuminemia was observed in 56.25%, 21.87%, 25% & 46.87% patients respectively. Kidney injury(KI) (Acute kidney injury or acute on chronic kidney disease) was observed in 68.75% patients, and mortality was 43.75%. MM patients with kidney injury (MM-KI) belonged to older age (63.77±11.15) group than MM patients with normal kidney functions (MM-NKF) (59.5±14.5 (p=0.255), their mean creatinine was 1.8(1.65) mg/dl, & proteinuria was 255.5(450.25) mg/day. Nine patients (40.90%) require renal replacement therapy in form of hemodialysis during course of treatment, and 18(81.81%) patients had full or partial recovery of renal functions. Mean hemoglobin & albumin was statistically significantly low in MM-KI group than MM-NKF, however fracture & anemia was more frequent among MM-NKF group, but statistically insignificant. Overall one, three & five-year survival rate for MM patients was 97%, 81% & 62% respectively. Conclusion: Our study showed that higher mortality was observed in MM patients with kidney injury. Early intervention of kidney injury predisposing factors may affect the renal & mortality outcome. This is one of few reported data on MM patients in UAE, we hope that further studies involving multicentric approach in MM patients could provide more detailed overview of kidney disease in these patients.